Polymorphism of four microsatellites and their polymerization effect on litter size in Boer goats - Wang, Jian Gang; Hou, Jin-Xing; Li, Guang; Zhu, Guang-Qin; Cao, Bin Yun (Electronic Journal of Biotechnology, 2013)
Background: Finding molecular markers linked to quantitative trait loci is the first step in marker-assisted selection (MAS). Microsatellites are excellent molecular markers because of their large numbers, even distribution in the genome, and high polymorphism. In this study, the polymerisation effect of four microsatellites (OarAE101, BM1329, BM143, and LSCV043) on litter size was analysed using microsatellite markers and pedigrees. Results: The results indicate that the polymerisation effect of four microsatellite loci significantly affected the litter size. E5E10F2F6G1G5H6H11 and E3E8F5F7G1G5H3H9 had the highest and lowest litter sizes in the F2 generation, respectively. The polymerisation effect value (v) of the E5E10 genotype was 3.18% higher than that of the E2E7 genotype. The v of genotype F2F6 was 14.47% higher than that of the F5F7 genotype. The v of genotype G1G5 was 58.99% higher than that of the G2G7 genotype. The v of the H6H11 genotype was 5.60% to 49.74% higher than those of the H4H10 and H1H7 genotypes. The v of the H3H9 genotype was 17.22% higher than that of the H1H7 genotype. Conclusions: The results of the present study are vital to improving the reproductive performance in goat breeds MAS.